Catastrophic femoral head trunnion dissociation: a case series with surface wear analysis. Issue 5 (September 2019) - Wood, Thomas J; Alzahrani, Mohammad; Langohr, Daniel; Teeter, Matthew G; Howard, James L; Schemitsch, Emil H; Lanting, Brent A
Introduction: Modular designs enhance accuracy of limb length and offset during total hip arthroplasty. However, such interfaces can be the site of corrosion and implant failure. The purpose of this study was to review 5 cases of catastrophic femoral head trunnion dissociation to better understand clinical and implant related risk factors for this complication. Methods: We describe 5 cases of femoral head dissociation following significant trunnion wear. Patient and implant related factors are reviewed. Surface wear patterns were assessed using electron microscopy and wear patterns were described qualitatively. Results: Commonalties among 5 presented cases include male, age over 65 and increased BMI. All femoral heads were cobalt chromium with a head size of at least 36 mm or greater. 4 out of 5 had high offset. All stems were the same design. Surface wear analysis showed material removed initially on the inferomedial aspect of the trunnion where the femoral head contacted the stem. Conclusions: Femoral head dissociation secondary to failure of the trunnion is a rare complication. We show associations with older age, increased BMI and male patients with increased femoral head size and offset. Material is removed initially inferomedially and progresses to fracturing the superior aspect of the trunnion.